OBSTACLE AND WORK-RELATED FACTORS THAT AFFECT EMPLOYEE WELLBEING AT WORPLACES - Fadillah Ismail; Chan Shiau Wei (International Journal of Accounting, Finance and Business, 2024)
Nowadays, employees’ wellbeing is becoming a popular topic in the world. The employer takes the wellbeing of their workers as a significant topic as a wellbeing worker can increase their productivity and improve the organization’s performance. However maintaining wellbeing are also challenging because there are many obstacle that preventing wellbeing at work place. Therefore, this paper is designed to explore about what is wellbeing and why should organizations care about wellbeing. The types at workplaces, what is the major obstacle and factors that affect employee wellbeing in the workplace are also being discussed in this article. There are six types of wellbeing that an employee should granted, which included the physical wellbeing, social wellbeing, mental health wellbeing, life satisfaction wellbeing, emotional wellbeing, and psychological wellbeing. Major obstacle preventing wellbeing in the workplace such as Cost Barrier, awareness, time management, practice management, discrimination and Organizational Policies/Practices. It has been identified that there are six domain factors that affect employee wellbeing at workplaces. Besides, there are some advantages brought by wellbeing to the organization, which increasing employee resilience, employee engagement, reducing absenteeism due to illness, and hence increasing the performance and productivity of employee. Employee is an asset to the company. To ensure the success of the company or businesses, wellbeing at the workplace is an important element to achieve it. Organization need to pay more attention and take as much action as possible so that wellbeing can be maintain and improved. In a nutshell, an organization should care about the employees’ wellbeing at the workplace to ensure that their workers are free of stress and able to improve productivity